Proficient Node Scheduling Protocol for Homogeneous and Heterogeneous Wireless Sensor Networks - R. Saravanakumar; N. Mohankumar; J. Raja (International Journal of Distributed Sensor Networks)
Recent communications in wireless sensor networks (WSNs) have much new energy-efficient protocols specifically designed, where energy awareness is an essential consideration. In WSNs, large numbers of tiny sensor nodes are used as an effective way of data gathering in various environments. Since the sensor nodes operate on battery of limited power, it is a great challenging aim to design an energy-efficient routing protocol, which can minimize the delay while offering high-energy efficiency and long span of network lifetime. Low energy adaptive clustering hierarchy (LEACH) is one of the clustering key routing techniques used to reduce energy consumption. In this paper, we propose an energy-efficient node scheduling reclustering algorithm in clusters and rotating cluster-head positions to evenly distribute the energy load among all of the nodes by the node scheduling concept of node active and sleep system in both homogeneous and heterogeneous methods to get energy-saving result. Our proposed model is enhanced from LEACH protocol by adapting node scheduling scheme (active and sleep) in homogeneous and heterogeneous node topologies of WSNs, which yield better performance in energy saving and increased network lifetime. This node scheduling scheme is properly implemented, and simulation results show that our proposed model is giving improved energy efficiency and prolongs the lifetime of WSNs.